Kandaulos. The testimony of select sources - Kokoszko, Maciej; Gibel-Buszewska, Katarzyna (Studia Ceranea, 2011)
The current study attempts to trace the history and retrieve the recipe of a specific dish called kándaulos/kándylos. It was a Greek delicacy developed in Lydia and named after a Lydian ruler, known by the name Candaules. The dish was (by means of the Greek Ionians in habiting Asia Minor) borrowed by the Greeks to have been established in the areas of the southern Balkan Peninsula by the 5th c B C. It became especially popular in the Hellenistic period. The testimony of the sources provides us with the information on two specific varieties of kándaulos/kándylos. The first was savoury and included such ingredients as cooked meat, stock, Phrygian cheese, breadcrumbs and dill (or fennel). The other recipe included milk, animal fat, cheese and honey. The dish is reported by the authors of the sources to have been costly and indicating the social status of its consumers. Although there is enough evidence indicating its popularity in antiquity, we lack reliable evidence showing that kándaulos/kándylos was still served in Byzantine times. However, Byzantine authors preserved the most detailed literary evidence on the delicacy.